2021
DOI: 10.3758/s13428-021-01544-2
|View full text |Cite
|
Sign up to set email alerts
|

Eye-tracking glasses in face-to-face interactions: Manual versus automated assessment of areas-of-interest

Abstract: The assessment of gaze behaviour is essential for understanding the psychology of communication. Mobile eye-tracking glasses are useful to measure gaze behaviour during dynamic interactions. Eye-tracking data can be analysed by using manually annotated areas-of-interest. Computer vision algorithms may alternatively be used to reduce the amount of manual effort, but also the subjectivity and complexity of these analyses. Using additional re-identification (Re-ID) algorithms, different participants in the intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Based on this, this study further investigates subjects’ interest experience in digital landscape roaming scenarios. The change trend in the interest degree of the five groups of virtual landscape scene nodes confirms that the subjects had the highest interest degree in the ancient tree ecological area during the immersion experience, which is consistent with the research of Hessels et al (2016) and Jongerius et al (2021) [ 61 , 62 ]. Wang et al analyzed the correlation between subjects’ interest in AOI.…”
Section: Discussionsupporting
confidence: 89%
“…Based on this, this study further investigates subjects’ interest experience in digital landscape roaming scenarios. The change trend in the interest degree of the five groups of virtual landscape scene nodes confirms that the subjects had the highest interest degree in the ancient tree ecological area during the immersion experience, which is consistent with the research of Hessels et al (2016) and Jongerius et al (2021) [ 61 , 62 ]. Wang et al analyzed the correlation between subjects’ interest in AOI.…”
Section: Discussionsupporting
confidence: 89%
“…Our dynamic region of interest (dROI) analysis of social attention relied on automatic face and body detection algorithms developed by Cao and colleagues (OpenPose: 30 ). We verified the accuracy of this algorithm on our video data by comparing its detections to manual coding of body presence by four human observers and found a high level of agreement (see Supplementary Materials Section 1.1 ; see also 34 ).
Figure 1 Dynamic region of interest (dROI) analysis of social attention while navigating a university campus.
…”
Section: Resultsmentioning
confidence: 69%
“…However, these algorithm based approaches are limited when evaluating gaze behaviors in locomotor settings as classifying gaze behaviors based exclusively on eye orientation may not account for disparity between the participants eye and bodily motion ( Hessels et al, 2018 ; Lappi, 2015 ). As such, as a person moves through the environment, determining point of gaze relative to environmental features has predominantly been achieved by frame-by-frame analysis of scene camera footage ( Hessels, Benjamins, et al, 2020 ; Jongerius et al, 2021 ; Kothari et al, 2020 ). In particular, a frame-by-frame approach has been commonly applied to consider the amount of time a person's point of gaze is located on designated environmental locations ( Ellmers et al., 2016 , 2020 ; Mele & Federici, 2012 ; Parr et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that frame-by-frame analysis methods are prone to inter-observer error and have been considered time consuming ( Duchowski, 2007 ; Hessels, Niehorster, et al, 2020 ; Kiefer et al, 2017 ). Further, researchers evaluating eye-tracking data analysis have recently noted that eye-tracking research would benefit from more standardized analysis procedures to enhance comparison between studies and assessment of study quality ( Jongerius et al, 2021 ). The capacity of optoelectronic data collection to express both point of gaze and the location of environmental features within a world-centered reference frame addresses these points by facilitating greater automation of the data analysis process, which promotes time efficiency, reduces inter-observer error, and greatly increases the number of trials that can be analyzed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation